ANALISIS KEPUASAN KERJA DAN TURNOVER INTENTION PADA AWAK KAPAL NIAGA NASIONAL - Samekto, Agus Aji (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2025)
This study aims to analyze the influence of job satisfaction on turnover intention among merchant marine crews in Indonesia. As one of the world's largest suppliers of seafarers, Indonesia plays a crucial role in the global maritime industry. However, this profession faces unique challenges such as isolation, high workloads, and prolonged separation from family, which significantly impact job satisfaction and the intention to leave the job. This research employs a quantitative approach with a correlational design. Data were collected through an online survey distributed to active national merchant marine crews, using standardized instruments: the Minnesota Satisfaction Questionnaire (MSQ) to measure job satisfaction and the Turnover Intention Scale (TIS) to measure turnover intention. Data analysis was conducted using simple linear regression techniques. The analysis results indicate a significant negative relationship between job satisfaction and turnover intention. This finding suggests that higher levels of job satisfaction experienced by seafarers correspond to a lower tendency to leave their profession or company. The practical implication of this study is the importance for national shipping companies not only to meet the minimum compensation standards regulated by the government but also to invest in motivator factors such as a supportive social work environment, performance recognition, and clear career paths to enhance the retention of qualified crew members and ensure the operational sustainability of the national shipping industry. Keywords: Job Satisfaction, Turnover Intention, Seafarers, Maritime Industry, Organizational Psychology